Effectiveness of the problem-based learning model to improve mathematical literacy of junior high school students - Farhana, Atika; Yuanita, Putri; Kartini, Kartini (Jurnal Gantang, 2025)
Existing studies show that learning using problem-based learning teaching modules can significantly improve mathematical literacy in class VII students at SMPN 1 Kampar. A quasi-experimental design was used, with the research population consisting of VII-grade students of SMPN 01 Kampar. The research sample consisted of two classes: VII-B, the control class, and VII-A, the experimental class. The data analysis technique employed was a posttest analysis of the results from the mathematical literacy test, using the t-test to determine whether there was an increase in performance, as indicated by N-Gain data. The results of data analysis showed that the Independent Sample t-test obtained a significance value of 0.001, which means that there is a significant difference between the control class and the experimental class. The average value of N-Gain was 0.6722 for the experimental class, categorized as medium, and 0.2970 for the control class, also categorized as medium. Indicates that learning using the PBL model increases mathematical literacy higher than classes that do not use the PBL model. These findings reveal that there is an increase in mathematical literacy, thus indicating that the use of the PBL model helps improve mathematical literacy.